Endogean and cavernicolous Coleoptera of the Balkans. XII. New species of Paramaurops Jeannel, 1948 (Coleoptera: Staphylinidae: Pselaphinae) from Macedonia - Hlaváč, Peter (Zootaxa, 2013)
The new species of the tribe Amauropini, Paramaurops vonickai n. sp. is described from Macedonia.